Description of student science process skills on temperature and heat practicum - Tanti Tanti; Dwi Agus Kurniawan; Rahmi Putri Wirman; Retno Wulan Dari; Eva Yuhanis (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
This study aimed to describe the science process skills of Senior High School 8 Muaro Jambi students on temperature and heat material (shape changes). The approach used in this study is an approach with a quantitative method that uses a research design using Survey Research design. The sample used in this study was Senior High School 8 Muaro Jambi, totaling 96 students of grade XI MIPA 1 to XI MIPA 3 odd semester 2019/2020. Data collection techniques in this study were observation and interviews. The observations of students' mastery of science process skills showed a percentage of 55.2% classified as poor. This means that students have low process skills. The lack of students' process skills is because the teacher dominates the learning process more. The learning process is still oriented towards mastering the material, and rarely does the experiment. This is in line with interviews conducted by researchers.